Kualitas Pelayanan dan Bauran Pemasaran Terhadap Kepuasan Pasien Rumah Sakit Ibu Anak Asih Jakarta Selatan - Utami, T. Annisa; Hilmy, M. Reza (Journal of Hospital Management, 2020)
Patient Satisfaction becomes the measurement of the success of a hospital, based on the data of Ibu Asih Hospital South Jakarta, the number of inpatient visits has decreased significantly in 2014 to 2016. This becomes an issue that must be considered by Hospital Management. The purpose of this study is to determine the effect of Service Quality and Marketing Mix both partially and jointly to the Satisfaction of Inpatients at at Ibu Anak Asih Hospital, South Jakarta. The research method used in this research is descriptive associative with quantitative approach, that is by describing the condition of the respondent and the description of research variables in the frequency table and the percentage of the questionnaire distributed by means of data analysis procedure. The sample in this study using simple random sampling technique with total sample of 100 respondents. Data analysis techniques use multiple linear regression. Research design using One-shot case study That is an experiment conducted without any comparison group and also without any preliminary test. The results showed that: (1) There is a positive influence and significant Quality of Service to Patient Satisfaction. (2) There is a positive and significant effect of Marketing Mix on Patient Satisfaction. (3) there is a positive influence and significant Quality of Service and Marketing Mix simultaneously to Patient Satisfaction. The findings of research results in this study is the highest indicator of marketing mix is a promotion with an average value of 4.4 while the lowest is the price with an average value of 3.98. The implications of this research are; (1) Quality of Service which is reflected by high reliability indicator hence can increase patient's satisfaction; (2) Marketing mix that is reflected by the high indicator of physical evidence can increase patient satisfaction.Keyword: Service Quality, Marketing Mix and Patient Satisfaction.